Study on the background characteristics of electric fields constrained by cross-sphere observations - MuPing Yang; XueMin Zhang; XuHui Shen; Yu Yuan; Tao Chen; JinLei Li; XinYan Ouyang; TongXia Li (Earth, Planets and Space)
Abstract The interactions among Earth’s spheres constitute both the starting point and ultimate goal of Earth system science research. An in-depth investigation into these interactions is essential for advancing the interdisciplinary integration and collaborative development of Earth sciences across various directions and scales. This study selected geoelectric field, atmospheric electric field, and ionospheric electric field data from three observation regions within mainland China to systematically investigate the background characteristics of electric fields constrained by cross-sphere observations, as well as their coupling relationships. The results reveal the following: (1) the diurnal variations of the geoelectric field and atmospheric electric field in the three observation regions demonstrate a “double-peak and single-valley” structure, with the timing of peaks and valleys closely related to sunrise, solar noon, and sunset. Additionally, the amplitude of diurnal variations shows a distinct seasonal pattern. (2) The annual variations of the ionospheric electric field align well with those of the geoelectric fields and atmospheric electric fields during the daytime, while the alignment is less effective at night. (3) The dominant periodic amplitudes of geoelectric fields and atmospheric electric fields are concentrated at 6-h, 8-h, 12-h, and 24-h cycles, which are closely associated with solar and lunar tidal effects. This study reveals that the geoelectric field, atmospheric electric field, and ionospheric electric field all exhibit significant diurnal, seasonal, and annual variations. Harmonic components of solar and lunar tides are present in the cross-sphere electric fields, reflecting the combined influence of solar and lunar tides on the lithosphere, near-surface atmosphere, and middle-to-upper atmosphere. However, the consistency of annual variations in electric fields is significantly affected by localized environmental factors. This research provides critical scientific insights into the coupling mechanisms and background characteristics of cross-sphere electric fields. Graphical Abstract